PENINGKATAN PENDAPATAN DAN KEMANDIRIAN EKONOMI IBU RUMAH TANGGA MELALUI BISNIS YOGHURT - Ayu Sitanini; Afif Hendri Putranto; Victor Bintang Panunggul; Niken Arimurti; Siska Irma Budianti (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
Processing milk into yogurt provides an opportunity for food diversification that can be developed into a value-added home-based microenterprise. However, the development of this opportunity is often constrained by limited production skills and inadequate understanding of basic business feasibility among community members. This community service program aimed to strengthen the technical skills of women in yogurt production while introducing basic economic literacy to support household-based entrepreneurship. The program involved 15 women from RT 03 RW 10, Bancarkembar Village, North Purwokerto District, Banyumas Regency, Indonesia, and was implemented using a Participatory Rural Appraisal (PRA) approach through community engagement, hands-on training (learning by doing), and participatory evaluation. Participants practiced yogurt processing based on food hygiene principles and conducted a simple business feasibility simulation covering initial investment, production costs, selling price, projected profit, and Break Even Point (BEP). The program was characterized by active participant involvement and improved understanding of yogurt fermentation techniques and its potential as a household-based business opportunity. Based on the simulation conducted during the training, yogurt production was estimated to generate a monthly net profit of IDR 6,918,337 with an investment payback period of approximately 25 days. The integration of food processing training and business feasibility analysis represents the main contribution of this program by combining technical competency development with economic literacy to support the growth of sustainable home-based food microenterprises. ABSTRAKPengolahan susu menjadi yoghurt menawarkan peluang diversifikasi pangan yang dapat dikembangkan sebagai usaha rumah tangga bernilai tambah. Namun, pemanfaatan peluang tersebut masih menghadapi kendala berupa keterbatasan keterampilan produksi dan rendahnya pemahaman masyarakat mengenai aspek kelayakan usaha. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kapasitas ibu rumah tangga dalam memproduksi yoghurt sekaligus memperkenalkan analisis ekonomi sederhana sebagai dasar pengembangan usaha pangan olahan. Program dilaksanakan dengan melibatkan 15 ibu rumah tangga di RT 03 RW 10 Kelurahan Bancarkembar, Kecamatan Purwokerto Utara, Kabupaten Banyumas melalui pendekatan Participatory Rural Appraisal (PRA) yang mencakup sosialisasi, praktik langsung (learning by doing), dan evaluasi partisipatif. Peserta mempraktikkan proses pembuatan yoghurt berdasarkan prinsip higiene pangan serta mengikuti simulasi kelayakan usaha yang meliputi investasi awal, biaya produksi, harga jual, laba, dan Break Even Point (BEP). Hasil kegiatan menunjukkan keterlibatan aktif peserta selama pelatihan serta peningkatan pemahaman mengenai teknik fermentasi dan peluang pengembangan yoghurt sebagai usaha rumah tangga. Berdasarkan simulasi kelayakan usaha, produksi yoghurt diperkirakan menghasilkan laba bersih sebesar Rp6.918.337 per bulan dengan periode pengembalian investasi sekitar 25 hari. Integrasi pelatihan teknologi pengolahan pangan dan literasi ekonomi menjadi kontribusi utama kegiatan ini dalam mendukung pengembangan UMKM berbasis pangan olahan di tingkat rumah tangga.